Gender and Reproductive Labor Migration in Asia, 1960–2000. Issue 2 (2nd April 2016) - Malhotra, Ragini Saira; Misra, Joya; Leal, Diego F.
Abstract : Studies on gender and migration have focused on how and why men and women migrate. While women often migrate for family reunification, they increasingly do so for their own work and economic opportunities. Studies on women's migration flows are rare; those that exist neglect increasingly prominent migration dynamics within Global South. Addressing this gap, we map understudied women's migration flows within Asian sub-regions from 1960–2000. Building on qualitative studies, we consider what these quantitative flows suggest about women's migration, and their involvement in reproductive labor–care, domestic, and entertainment work, and marriage migration–in the context of bilateral migration policies. We find high volume flows, even if not feminized, are directed primarily from countries in South and Southeast Asia to countries in West Asia, East Asia, and Southeast Asia. We find strong evidence that within Asia, transnational migration has become increasingly feminized and diversified since the 1960s. Variations in women's migration flows, among countries and over time, suggest a growing demand for women migrants. Mapping these regional flows provides a more comprehensive understanding of women's migration within the Global South. Our findings reaffirm, complicate, and deepen accounts about labor exportation and migration policies that support a transnational reproductive labor economy.